Elektronski zdravstveni zapis in "online" zdravstvene storitve v osnovnem zdravstvu - Iljaž, Rade (Informatica Medica Slovenica, 2005)
Electronic health records or electronic patient records in primary health caresystems of developed world arose about two decades ago. The needs for their further development could be dramatically different depending on viewingangle. The most important are viewing angle of patient as user of health care services, the one of physicians', and finally the state's or community's angle of sight. The basic goal is professional support during the lifelong health care of individuals as well of whole community. Slovenia and its health care system has to face with many challenges of EU e-health action plan, in the following years,
Keywords: Computer Communication Networks; elektronska kartoteka; elektronski zapisi; informatizacija; Medical Records Systems, Computerized; Medicinske kartoteke, sistemi računalniški; osnovno zdravstvo; Osnovno, zdravstveno varstvo; pacienti; podatki; Primary Health Care; Računalniške mreže; zdravstvo